Polsko-niemiecka współpraca służb policyjnych (lubuskie-Brandenburgia) = Polish-German cooperation of police services (Lubuskie Voivodship-Branderburg) - Krystians, Piotr (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Crime does not recognize territorial boundaries. This statement has taken on a new dimension as a result of political transformations initiated in 1989. Poland had to face not only positive, and undoubtedly prevailing, changes in the political, social and economic spheres, but also negative aspects of the transformation process (among the others: the rapid development and activity of organized crime groups). The border areas, especially the ones situated along the Polish-German border (until 2004 - EU external border) were particularly vulnerable to the above mentioned dangers in the first years of transformation.
Keywords: pogranicze polsko-niemieckie; stosunki polsko-niemieckie; współpraca polsko-niemiecka; współpraca regionalna; policja